Objective Calls Under the Spotlight: Referee Consistency and Behaviour on Football's Biggest Stage - David Butler; Robert Butler; Carl Singleton (Institute of Labor Economics (IZA), 2025)
We study the objectivity of officiating under extreme pressure by analysing additional time played at the 2022 FIFA World Cup and 2024 UEFA European Championship. Controlling for within-match events, rules should be applied consistently across both halves of a football match. However, we argue that second-half time allocations could be increased by greater social pressure, intensity, and stakes, as final payoffs become imminent. Our analysis shows that, even after accounting for major stoppages and events – and despite identical rules – referees add substantially more time in the second half than the first. Moreover, referees allow more stoppage time when the scoreline is close in the second half, but only at the World Cup because tight contests were cut short there in the first halves. These discrepancies raise concerns about the effectiveness of time-wasting strategies in the sport. More broadly, our results contribute to the discussion of decision-making under pressure and implicit biases in high-stakes environments.
Keywords: D01; D91; L83; Z20; 330; decision making; judgement; bias; pressure; additional time